1995
DOI: 10.1001/jama.1995.03520260039030
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of the Systemic Inflammatory Response Syndrome (SIRS)

Abstract: This prospective epidemiologic study of SIRS and related conditions provides, to our knowledge, the first evidence of a clinical progression from SIRS to sepsis to severe sepsis and septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
387
1
18

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,623 publications
(443 citation statements)
references
References 21 publications
11
387
1
18
Order By: Relevance
“…However, this is not surprising, as we studied only severely ill patients who had septic shock. Previous studies have shown that the severity of sepsis correlates with the incidence of kidney injury [4]. The incidence of acute kidney injury we report is substantially higher than the incidence in the most severely ill patients described by Rangel-Frausto et al [4], which may reflect between study differences due to case mix, or a true increased incidence of acute kidney injury in sepsis today compared with the past, as has been suggested by others [20].…”
Section: Incidence and Outcome Of Acute Kidney Injurysupporting
confidence: 53%
See 2 more Smart Citations
“…However, this is not surprising, as we studied only severely ill patients who had septic shock. Previous studies have shown that the severity of sepsis correlates with the incidence of kidney injury [4]. The incidence of acute kidney injury we report is substantially higher than the incidence in the most severely ill patients described by Rangel-Frausto et al [4], which may reflect between study differences due to case mix, or a true increased incidence of acute kidney injury in sepsis today compared with the past, as has been suggested by others [20].…”
Section: Incidence and Outcome Of Acute Kidney Injurysupporting
confidence: 53%
“…Previous studies have shown that the severity of sepsis correlates with the incidence of kidney injury [4]. The incidence of acute kidney injury we report is substantially higher than the incidence in the most severely ill patients described by Rangel-Frausto et al [4], which may reflect between study differences due to case mix, or a true increased incidence of acute kidney injury in sepsis today compared with the past, as has been suggested by others [20]. The high incidence we observed may also reflect greater sensitivity of the RIFLE definitions compared to older definitions of renal failure.…”
Section: Incidence and Outcome Of Acute Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis, severe sepsis, and septic shock are more frequent in the ICU than in other sections of a healthcare institution (22)(23)(24)(25). Several reports have confirmed that severe sepsis is found in 2% of patients admitted to the general ward, while it is found in up to 75% of ICU patients (18,20,26,27).…”
Section: Discussionmentioning
confidence: 98%
“…Current understanding views death from multiorgan failure as the extreme consequence of stresses that induce a systemic inflammatory response syndrome (eg endotoxin, burns, mechanical trauma). [32][33][34] Evidence argues that the monocyte/macrophage system processes the inflammatory stimulus, 35,36 and then initiates and amplifies subsequent cytokine cascades. 37,38 Under certain conditions, this can lead to loss of control, functional immune paralysis, [39][40][41] or in the metaphor of Bone, 42 'immunologic dissonance'-a pathological imbalance between pro-and counter inflammatory molecules.…”
Section: Discussionmentioning
confidence: 99%